Development and validation of a hypoxia- and mitochondrial dysfunction- related prognostic model based on integrated single-cell and bulk RNA sequencing analyses in gastric cancer - Li, Yirong; Cui, Yue; Wang, Zhen; Wang, Liwei; Yu, Yi; Xiong, Yuyan (Frontiers in Immunology, 2024)
Gastric cancer (GC) remains a major global health threat ranking as the fifth most prevalent cancer. Hypoxia, a characteristic feature of solid tumors, significantly contributes to the malignant progression of GC. Mitochondria are the major target of hypoxic injury that promotes mitochondrial dysfunction during the development of cancers including GC. However, the gene signature and prognostic model based on hypoxia- and mitochondrial dysfunction-related genes (HMDRGs) in the prediction of GC prognosis have not yet been established. In this study, the scRNA-seq and bulk RNA-seq data from stomach cancer cohorts were analyzed to identify HMDRGs. Five HMDRGs (ZFP36, SERPINE1, DUSP1, CAV1, and AKAP12) were identified by performing the least absolute shrinkage and selection operator Cox (LASSO-Cox) regression analysis. A prognostic risk model was established to be able to stratify GC patients into high- and low-risk groups based on the median value of the risk scores. A nomogram model for predicting overall survival (OS) was developed, and it demonstrated consistent results with the actual observed OS. The ESTIMATE, CIBERSORT, and ssGSEA analyses were performed to evaluate immune infiltration, showing that individuals in the high-risk group tend to promote immune cell infiltration. Moreover, cancer immunotherapy evaluated by tumor immune dysfunction and exclusion (TIDE) and immunophenoscore (IPS) demonstrate that the high-risk group patients exhibit poorer responses to cancer immunotherapy compared to the low-risk group. Immunohistochemistry (IHC) staining indicated that the expression levels of HMDRGs were remarkably correlated with GC, of which, SERPINE1 displayed the most pronounced up-regulation, while ZFP36 exhibited the most notable down-regulation in GC patients. Furthermore, in vitro investigation validated that SERPINE1 and ZFP36 contribute to the malignant processes of GC cells correlated with mitochondrial dysfunction. This study presents a novel and efficient approach to evaluate GC prognosis and immunotherapy efficacy, and also provides insights into understanding the pathogenesis of GC.